Robust spin liquidity in 2D metal-organic framework Cu3 (HHTP)2 with S=1/2 kagome lattice - Ninawe, Pranay; Jain, Anil; Sangole, Mayur; Anas, Mohd; Ugale, Ajay; Malik, Vivek K.; Yusuf, Seikh M.; Singh, Kirandeep; Ballav, Nirmalya (Chemistry- a european journal, 2024)
On one hand electron or hole doping of quantum spin liquid (QSL) may unlock high-temperature superconductivity and on the other hand it can disrupt the spin liquidity, giving rise to a magnetically ordered ground state. Recently, a 2D MOF, Cu-3(HHTP)(2) (HHTP - 2,3,6,7,10,11-hexahydroxytriphenylene), containing Cu(II) S = 1/2 frustrated spins in the Kagome lattice is emerging as a promising QSL candidate. Herein, we present an elegant in situ redox-chemistry strategy of anchoring Cu-3(HHTP)(2) crystallites onto diamagnetic reduced graphene oxide (rGO) sheets, resulting in the formation of electron-doped Cu-3(HHTP)(2)-rGO composite which exhibited a characteristic semiconducting behavior (5 K to 300 K) with high electrical conductivity of 70 S . m(-1) and a carrier density of similar to 1.1 x 10(18) cm(-3) at 300 K. Remarkably, no magnetic transition in the Cu-3(HHTP)(2)-rGO composite was observed down to 1.5 K endorsing the robust spin liquidity of the 2D MOF Cu-3(HHTP)(2). Specific heat capacity measurements led to the estimation of the residual entropy values of 28 % and 34 % of the theoretically expected value for the pristine Cu-3(HHTP)(2) and Cu-3(HHTP)(2)-rGO composite, establishing the presence of strong quantum fluctuations down to 1.5 K (two times smaller than the value of the exchange interaction J).
Keywords: 2D Metal-organic Framework; Electron doping; Reduced graphene oxide; Spin Liquid; Spin-frustration